MEDIATION ROLE OF SOCIAL MEDIA ADOPTION ON THE ORGANIZATIONAL INNOVATIVENESS AND SMEs PERFORMANCE IN NORTH-WESTERN NIGERIA - ABUBAKAR, ABDULKADIR; IDRIS, BASHIR BUGAJE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The study seeks to examine the relationship between organizational innovativeness and SME performance and the mediating effect of social media adoption. Statistical analyses were based on the data collected, through a survey questionnaire from 396 SMEs in North western Nigeria. The Partial Least Square (PLS) method was used to investigate the relationship between the study variables. The study found that the direct impact of organizational innovativeness is not significantly correlated with SME performance, social media is significant in mediating the relationship between organizational innovativeness and the SME’s performance and context-specific nature necessitates tailoring strategies based on industry-specific conditions, market characteristics, and technological landscapes. The study concluded that organizational innovativeness exhibited relatively modest effects on SME performance, and social media adoption as a mediator unveiled a statistically significant relationship, highlighting the pivotal role of social media in influencing SME performance within the context of organizational innovation. Finally, the study recommends that SMEs should emphasize the incorporation of social media platforms as integral components of innovation strategies within SMEs, consider holistic approaches that incorporate diverse elements such as social media adoption to enhance the effectiveness of innovation strategies and encourage SMEs to invest in technological adoption beyond traditional innovation practices.